A Study on Relationship between Inflation and Money Market Rates in India - Kaur, Simarpreet; Kaur, Navkiranjit (Gyan Management Journal, 2018)
The operations in the Money Market are generally short term in nature. Money Market is a market for short-term funds with maturities ranging from overnight to one year and includes financial instruments that are considered to be close substitutes of money. In India, Money Market rates are very fluctuating due to number of factors such as GDP, CPI, interest rates, money supply, exchange rates etc. This paper explores the relationship between inflation and money market rates for the period from April 2015 to March 2017. It has used regression for analysis of data. Results from analysis indicate that growth in prices greatly affects the lending rates of short term financial instruments thus making borrowings costlier for the market participants. It also suggested that government should take quick steps to curb rising inflation in order to achieve the sustainable economic growth of the country.
Keywords: Money Markets; CPI; Call Money Market; Certificate of Deposits (CD's); Commercial Papers (CP's)